2019
DOI: 10.1186/s13052-019-0628-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preptin peptide level in the sera of rachitic children and in breast milk of their mothers

Abstract: Background Preptin is a 34-residue pancreatic hormone that stimulates osteoblast proliferation and reduces osteoblast apoptosis. Research aims To measure levels of serum Preptin in rachitic children and in breastmilk of their mothers and to compare with levels in healthy non-rachitic children. Methods Thirty children with rickets and another 30 non-rachitic age and sex matched controls were subjected to detailed history, physical examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Serum preptin and breast milk preptin were found to be lower in rachitic children and their mothers, respectively, when compared to non-rachitic subjects. 113 Serum preptin levels are decreased in both men and women with osteoporosis and positively correlate with bone mass density. 114,115 It is therefore likely that a lower activity of preptin is involved in the pathogenesis of osteoporosis, affecting bone formation rather than bone resorption.…”
Section: Bone Mineral Metabolismmentioning
confidence: 99%
“…Serum preptin and breast milk preptin were found to be lower in rachitic children and their mothers, respectively, when compared to non-rachitic subjects. 113 Serum preptin levels are decreased in both men and women with osteoporosis and positively correlate with bone mass density. 114,115 It is therefore likely that a lower activity of preptin is involved in the pathogenesis of osteoporosis, affecting bone formation rather than bone resorption.…”
Section: Bone Mineral Metabolismmentioning
confidence: 99%
“…A significant positive correlation was found between preptin and lumbar spine and neck BMD, respectively, after adjustment for estradiol in both groups. Preptin was also negatively correlated with age in the whole group [ 76 , 79 , 80 ]. A recent article published in 2021 was the first to investigate the relationship between preptin and bone metabolism in hemodialysis patients [ 77 ] ( Table 2 ).…”
Section: The Impact Of Preptin On Bone and Calcium Metabolismmentioning
confidence: 99%
“…Bebars et al [ 79 ] found lower serum preptin levels in rachitic children compared to healthy controls. Preptin was inversely associated with ALP in rachitic patients, suggesting preptin may also mirror the severity of the disease, similar to ALP ( Table 2 ) [ 79 ].…”
Section: The Impact Of Preptin On Bone and Calcium Metabolismmentioning
confidence: 99%
See 1 more Smart Citation